Faktor Perilaku Yang Berhubungan Dengan Keberadaan Cimex spp Di Desa Purbayasa, Purbalingga Tahun 2021 - Dwi Agustin Ronawati; Retno Hestiningsih; Nissa Kusariana; Lintang Dian Saraswati (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background : Cimex can be found in mattress, sofa, and in place where wood exist. Cimex can cause health effects. Continuous Cimex bites can disturb individual comfort, entomophobia, allergies, and anemia. The existance of Cimex can be influenced by behavioral factors. Cimex is still found in Purbayasa Village. The absence of research on the Cimex survey in Purbayasa village makes this research necessary to increase public awareness about the dangers of cimex and their prevention. The purpose of this study is to analyze the relationship between behavior and the presence of CimexMethods : This study was a descriptive analytic study used visual survey method with cross sectional approach and a sample count of 53 randomly selected homes in RW 3. The survey of cimex by visual method. The data was obtained through respondents interviews with questionnaires and observation sheets with observation. Chi sqaure test is used to analyze the relationship between community behaviour and the presence of cimex Results :9,4% of respondents homes were positive bed bugs. The founded all bed bugs species is Cimex hemipterus. This study found that 79,2% of respondents had good knowledge, 75,5% had good attitudes, and 60,4% had good practices. There was no relation to the knowledge (α=0.05, ρ=0.000 ). The practice is also related to the presence of bed bugs (α=0.05, ρ=0.004 )Conclusion : It concluded that attitudes and practices are factors related to the presence of bed bugs.